1986
DOI: 10.1038/322799a0
|View full text |Cite
|
Sign up to set email alerts
|

Tight linkage between a splicing mutation and a specific DNA haplotype in phenylketonuria

Abstract: The first phenylketonuria mutation identified in the human phenylalanine hydroxylase gene is a single base substitution (GT----AT) in the canonical 5'-splice donor site of intron 12. Direct hybridization analysis using specific oligonucleotide probes demonstrates that the mutation is tightly associated with a specific restriction fragment-length polymorphism haplotype among mutant alleles. The splicing mutation is the most prevalent phenylketonuria allele among Caucasians, and the results suggest the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(93 citation statements)
references
References 14 publications
4
87
0
2
Order By: Relevance
“…These are absolutely conserved and required for accurate splicing of nuclear pre-mRNA (25,26). Mutations at the GT dinucleotide ofthe 5' splice site have been reported to cause skipping ofthe preceding exon (27)(28)(29)(30)(31). We concluded that the substitution of GT dinucleotide for TT in the 5' splice site of intron 8 caused the skipping of exon 8.…”
Section: Discussionmentioning
confidence: 86%
“…These are absolutely conserved and required for accurate splicing of nuclear pre-mRNA (25,26). Mutations at the GT dinucleotide ofthe 5' splice site have been reported to cause skipping ofthe preceding exon (27)(28)(29)(30)(31). We concluded that the substitution of GT dinucleotide for TT in the 5' splice site of intron 8 caused the skipping of exon 8.…”
Section: Discussionmentioning
confidence: 86%
“…We demonstrated a point mutation in the canonical 5' splice donor site of the first intron of the PBGD gene (Go-A). Similar mutations have been shown (19,20) to completely abolish normal splicing. Since the first intron interrupts the sequence coding for the nonerythroid isoform of PBGD (7), it is to be expected that an abnormal splicing leads to detrimental effects on that gene product.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that a previous study (9) demonstrated C3 concentrations between 17 and 58 ng/ml in the sera of three other unrelated caucasoid C3-deficient patients, levels that are below the detection limit of the present assay. However the studies of the gene structure and mRNA expression in our patient suggest (31)(32)(33) in the f3-globin gene, causing fl-thalassaemia; in the phenylalanine hydroxylase gene, causing phenylketonuria (34); and in the porphobilinogen deaminase gene, causing acute intermittent porphyria (35). The effects of naturally occurring mutations in the canonical GT 5' donor splice junction dinucleotide on RNA processing and subsequent protein expression are variable.…”
Section: Resultsmentioning
confidence: 99%